Satisfaction with community pharmacies services in Jordan: A cross-sectional study - Abdallah Y. Naser; Bayan Saleh Abu Sbeat (Elsevier, 2022)
Background: Pharmacists are responsible for giving patients basic information about their medications, as well as informing them about drug administration, safety, efficacy, medication storage, and promoting patient adherence to their medications. Patient satisfaction will undoubtedly improve if patient-centered care is used and the patient is encouraged to participate in the decision-making process. The aim of this study is to explore patients' satisfaction with the pharmacy, its location, medication handling, dispensing and counselling procedures, or other non-paid services. Method: This was a cross-sectional study that was conducted in Jordan using online questionnaire tool. Data was collected for the period between November 2021 and January 2022. A previously developed and validated questionnaire tool was used in this study. Binary logistic regression analysis was used to determine factors affecting satisfaction with community pharmacy services. Results: A total of 1,611 patients participated in this study. More than half of the patients (55.5%) were males. Around 50.0% of the patients were aged 30 years and below. Patients were moderately satisfied with community pharmacy services (the mean satisfaction score was 148.6 (SD: 19.4) out of 205 (maximum obtainable score), which is equal to 72.5%). Patients' satisfaction was relatively consistent across the four sub-scales, ranging from 68.0% (satisfaction with additional non-paid services) to 74.7% (for satisfaction with the store, location, and staff). Patients' satisfaction with the store, location, and staff, as well as satisfaction with dispensing and counselling methods, differed significantly by age, marital status, work status, and the existence of chronic disease history. Patients' satisfaction with drug handling varies significantly depending on the patients' age, marital status, education level, employment position, and the presence of a history of chronic conditions. Patients' satisfaction with additional non-paid services differed significantly depending on the patients' educational level alone. Patients aged between 24 and 30 years old, as well as university students, were more likely to be satisfied with community pharmacy services. Conclusion: In Jordan, patients were satisfied with community pharmacy services to a moderate degree. Future research should look on patient satisfaction with pharmaceutical services in hospitals. Furthermore, strategies to promote satisfaction with pharmaceutical services should be investigated.